Fuel consumption and emission evaluation of a rapid bus transport system at different operating conditions - Ozener, Orkun; Ozkan, Muammer (ELSEVIER SCI LTD, 2020)
The real driving emissions of vehicles have attracted great interest in recent years due to the increased environmental awareness. Public transport systems using internal combustion engines contributes greenhouse gases and harmful pollutants significantly. The routes of public transport mainly include urban areas with high population density. From this perspective, analyzing of the public transport systems real driving emissions is important for creating environmentally friendly cities. The economy of fossil fueled public transportation is another major concern that should be optimized. There are few studies focusing on the emission characteristics of public transport buses currently working on dedicated routes. In this context one of the biggest transport axle of the world, Metrobus Rapid Bus Transport system is analyzed. The Metrobus equipped with portable emission measurement systems and portable fuel consumption meter is used for measurement activities. Then the results are analyzed in terms of emissions and fuel consumption regarding to the operating parameters. The results showed that the driving behavior has great effect on both emissions and fuel consumption. It was shown that the accumulated emissions near bus stop can strongly affect the public health. The emissions and fuel consumption are both analyzed regarding to the acceleration and speed. The emissions and fuel factors are developed and compared with the values indicated in the literature. It was also analyzed that it is possible to lower emissions with operating the vehicle some certain regions.
Keywords: Real driving emissions; Fuel consumption; Public transportation; Diesel engine; Energy & Fuels; Engineering